Asphalt modified ethylene vinyl acetate waterproof coiled material and manufacturing process thereof

By mixing asphalt with modified ethylene vinyl acetate copolymer and uniformly mixing with polyvinyl chloride and other materials, plasticizing and extruding, a waterproof coil with improved temperature sensitivity and interface compatibility was prepared, and the current solution was solved In the art, asphalt has problems such as temperature sensitivity and poor interface compatibility, which have achieved higher low temperature resistance, high temperature resistance and corrosion resistance.

CN119463379AInactive Publication Date: 2025-02-18JIANGSU OUXIDUN TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411605948.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing polyvinyl chloride waterproof coils, asphalt is temperature sensitive, resulting in unstable performance, and poor interface compatibility with polyvinyl chloride, affecting its corrosion resistance, high temperature resistance and low temperature resistance.

Method used

Modified asphalt is prepared by mixing the asphalt with the modified ethylene vinyl acetate copolymer, and then uniformly mixing it with polyvinyl chloride and styrene-butadiene-styrene, and plasticized and extruded to obtain a matrix coil. The process includes soaking prefabricated polyester cloth and grid cloth in the slurry, performing composite treatment, traction, width adjustment and winding to form a waterproof coil.

Benefits of technology

Modified asphalt improves the flexibility and heat resistance of asphalt, enhances the low temperature and corrosion resistance of polyvinyl chloride coils, improves the interface compatibility between asphalt and polyvinyl chloride, and extends the use of waterproof coils. life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof coiled materials, and particularly discloses an asphalt modified ethylene vinyl acetate waterproof coiled material and a manufacturing process thereof. Comprising the following operation steps: S1) cleaning and drying polyester fabric, placing the polyester fabric in slurry at 40-50 DEG C, and performing ultrasonic soaking to obtain prefabricated polyester fabric; (2) the gridding cloth is cleaned and dried, and prefabricated gridding cloth is obtained; s2: (1) heating asphalt to a molten state, adding the modified ethylene-vinyl acetate copolymer, heating, uniformly mixing, shearing at a high speed for 20-30 minutes, then shearing at a low speed for 20-30 minutes, and incubating for 1-2 hours to obtain modified asphalt; (2) uniformly mixing polyvinyl chloride, modified asphalt and styrene-butadiene-styrene, plasticizing and extruding to obtain a matrix coiled material; and S3, the base body coiled material and the prefabricated polyester fabric are sequentially overlaid on the prefabricated gridding cloth, composite treatment, traction, width adjustment and rolling are sequentially conducted, and the waterproof coiled material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterproof membrane technology, specifically to an asphalt-modified ethylene vinyl acetate waterproof membrane and its manufacturing process. Background Technology

[0002] Polyvinyl chloride (PVC) is an inexpensive plastic with good mechanical properties and flame retardancy. However, it has poor toughness and easily releases hydrogen chloride gas when heated. Research has found that ethylene-vinyl acetate copolymers and crosslinking agents can improve the thermal stability and mechanical properties of PVC. Ideal PVC waterproof membranes possess advantages such as high toughness, oxidation resistance, high temperature resistance, and corrosion resistance, and are widely used in tunnels, roofs, and many other fields.

[0003] In order to prepare ideal polyvinyl chloride waterproof membranes, existing technologies often involve adding asphalt to polyvinyl chloride. However, asphalt is sensitive to temperature; it becomes soft and sticky at high temperatures and brittle at low temperatures, resulting in cracks. Furthermore, it has poor interfacial compatibility with polyvinyl chloride.

[0004] To solve this problem, it is of great significance to develop a waterproof membrane that is resistant to corrosion, high temperature, and low temperature. Summary of the Invention

[0005] The purpose of this invention is to provide an asphalt-modified ethylene vinyl acetate waterproof membrane and its manufacturing process, so as to solve the problems mentioned in the background art.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A manufacturing process for an asphalt-modified ethylene vinyl acetate waterproof membrane includes the following steps: S1: (1) Wash and dry the polyester fabric, place it in the slurry at 40~50℃, and ultrasonically soak it for 15~20 minutes to obtain the pre-made polyester fabric; (2) Wash and dry the mesh fabric to obtain the pre-made mesh fabric. S2: (1) Heat the asphalt to a molten state at 140~150℃, add the modified ethylene vinyl acetate copolymer, raise the temperature to 180~185℃, mix evenly, shear at a speed of 4500~6000r / min for 20~30 minutes, then shear at a speed of 500~600r / min for 20~30 minutes, and incubate at 160~170℃ for 1~2 hours to obtain the modified asphalt; (2) After uniformly mixing polyvinyl chloride, modified bitumen, and styrene-butadiene-styrene, plasticize and extrude to obtain the matrix roll material; S3: The base material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then subjected to composite treatment, traction, width adjustment and winding to obtain the waterproof membrane.

[0007] In a more optimized manner, the mass ratio of the asphalt to the modified ethylene vinyl acetate copolymer is (3~4):1; the raw materials of the matrix roll material include the following components: by weight, 60~70 parts of polyvinyl chloride, 10~15 parts of modified asphalt, and 8~12 parts of styrene-butadiene-styrene.

[0008] A more optimized method for preparing the modified ethylene vinyl acetate copolymer is as follows: (1) 6-amino-1-mercaptohexane hydrochloride, ethylene vinyl acetate copolymer, and AIBN are added to tetrahydrofuran, mixed uniformly, and irradiated under a 350nm, 100W ultraviolet lamp for 2-3 hours to obtain an intermediate product; (2) 4,4'-(hexafluoroisopropene) phthalic anhydride is added to N,N'-dimethylformamide and mixed uniformly to obtain solution A; under nitrogen protection, 4,4'-diaminodiphenyl ether is added to N,N'-dimethylformamide and mixed uniformly, solution A is added, and the mixture is reacted at room temperature for 30-40 minutes, heated to 150-160℃ and reacted for 2-3 hours, the intermediate product and aminated alumina are added and mixed uniformly, and the mixture is further reacted at 180-200℃ for 6-8 hours to obtain the modified ethylene vinyl acetate copolymer.

[0009] In a more optimized form, the raw materials for the intermediate product include the following components: by weight, 0.5 to 0.8 parts of 6-amino-1-mercaptohexane hydrochloride, 2 to 3 parts of ethylene vinyl acetate copolymer, 0.002 to 0.003 parts of AIBN, and 20 to 40 parts of tetrahydrofuran; The raw materials for the modified ethylene vinyl acetate copolymer include the following components: by weight, 4.42-4.45 parts of 4,4'-(hexafluoroisopropene)phthalic anhydride, 40-50 parts of N,N'-dimethylacetamide, 2-2.2 parts of 4,4'-diaminodiphenyl ether, 4.39-4.4 parts of intermediate product, and 3-5 parts of aminated alumina.

[0010] A more optimized method for preparing the slurry is as follows: S1: (1) After ball milling zinc nitrate and titanium dioxide for 20-30 minutes, add them to a 2-3M sodium hydroxide aqueous solution and mix evenly for 1-2 hours. Then calcine them at 600-650℃ for 2-3 hours to obtain composite nanoparticles; (2) Disperse the composite nanoparticles ultrasonically in toluene solution and react them at 100-120℃ for 20-22 hours. Add 3-aminopropyltriethoxysilane and continue the reaction for 8-10 hours to obtain aminated composite nanoparticles; (3) Add the aminated composite nanoparticles to N,N'-dimethylformamide and mix evenly. Add 4,4'-(hexafluoroisopropene) phthalic anhydride and react at room temperature for 30-40 minutes under nitrogen protection. Then raise the temperature to 150-160℃ and react for 2-3 hours. Mix evenly with 2,2-bis(4-aminophenyl)hexafluoropropane and raise the temperature to 180-200℃ to continue the reaction for 6-8 hours to obtain composite nanoparticle polymers; S2: The composite nanoparticle polymer, N-phenyl-N'-cyclohexyl-p-phenylenediamine, and N,N'-dimethylformamide are ball-milled for 2-4 hours at a temperature of 30-40℃ and a rotation speed of 800-1000 rpm to obtain a slurry.

[0011] More optimized, the mass ratio of zinc acetate to titanium dioxide is 3:(5~7); the mass ratio of the composite nanoparticles to 3-aminopropyltriethoxysilane is 1:(0.05~0.08); the raw materials of the composite nanoparticle polymer include the following components: by weight, 4~6 parts of aminated composite nanoparticles, 4.4~4.5 parts of 4,4'-(hexafluoroisopropene)phthalic anhydride, 6~7 parts of 2,2-bis(4-aminophenyl)hexafluoropropane, and 60~70 parts of N,N'-dimethylformamide.

[0012] In a more optimized form, the raw materials of the slurry include the following components: by weight, 15-20 parts of composite nanoparticle polymer, 3-5 parts of N-phenyl-N'-cyclohexyl-p-phenylenediamine, and 40-60 parts of N,N'-dimethylformamide.

[0013] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: The present invention uses polyvinyl chloride (PVC) as the base material. In order to improve the performance of the base material, the present invention uniformly mixes PVC, modified bitumen, and styrene-butadiene-styrene, and then plasticizes and extrudes the mixture to obtain the base material. The modified bitumen is made from bitumen and modified ethylene vinyl acetate copolymer.

[0014] In this invention, the vinyl groups on the ethylene vinyl acetate copolymer and the thiol groups on the 6-amino-1-mercaptohexane hydrochloride react via a click chemical reaction to introduce an amino group and obtain an intermediate product. The intermediate product is then introduced during the preparation of polyimide, and aminated alumina is used for end capping to obtain a copolymer of polyimide and ethylene vinyl acetate, referred to as modified ethylene vinyl acetate copolymer.

[0015] Among them, ethylene-vinyl acetate copolymer has excellent flexibility and elasticity, which can enhance the flexibility of PVC rolls, making them more adaptable and durable in applications. The introduction of polyimides containing fluorinated groups can improve the heat and cold resistance of PVC rolls, enabling them to maintain stable performance over a wider temperature range.

[0016] Aminated alumina can provide additional interfacial adhesion, enhance the adhesion between asphalt and PVC, reduce the separation of asphalt and PVC, and thus improve the aging resistance of the base material.

[0017] The addition of styrene-butadiene-styrene (SBS) further improves the interfacial compatibility between asphalt and PVC, and also enhances the softening point, aging resistance, and stability of asphalt, while maintaining its good adhesion, thus extending the service life of the waterproof membrane. Modified ethylene-vinyl acetate copolymers, through their excellent flexibility and elasticity, can significantly improve the performance of asphalt at low temperatures and reduce the brittleness of asphalt in low-temperature environments, thus contributing to improved low-temperature resistance of waterproof membranes.

[0018] The present invention involves sequentially stacking a base roll material and a prefabricated polyester fabric on a prefabricated mesh fabric, and then sequentially performing composite treatment, traction, width adjustment, and winding to obtain a waterproof roll material.

[0019] Polyester fabric shrinks at low temperatures, which affects the performance of waterproof rolls. To solve this problem, this invention prepares a slurry by combining composite nanoparticle polymer, N-phenyl-N'-cyclohexyl-p-phenylenediamine (anti-aging agent), and N,N'-dimethylformamide, and then soaks the polyester fabric in the slurry.

[0020] Among them, the composite nanoparticle polymer is made of composite nanoparticles obtained by zinc oxide and titanium dioxide, and then the composite nanoparticles are aminated. During the preparation of polyimide, the aminated composite nanoparticles and 2,2-bis(4-aminophenyl)hexafluoropropane are introduced for end capping to obtain the composite nanoparticle copolymer.

[0021] This method improves the dispersibility of composite nanoparticles in the slurry, facilitating their uniform filling of the pores in polyester fabric and reducing its shrinkage at low temperatures. The introduction of polyimide and the end-capping with 2,2-bis(4-aminophenyl)hexafluoropropane enhance the cold resistance and corrosion resistance of the polyester fabric. The synergistic introduction of zinc oxide and titanium oxide further improves the heat resistance and corrosion resistance of the polyester fabric. Furthermore, the white surface exhibits excellent solar reflectivity, reducing energy consumption. Detailed Implementation

[0022] The following are preferred embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. For those skilled in the art, all other embodiments obtained by those skilled in the art without creative effort without departing from the principles of the embodiments of the present invention are within the scope of protection of the present invention.

[0023] In the following specific embodiments, the parts are by weight. It should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: titanium dioxide (S26013), zinc nitrate (CAS 7779-88-6), 3-aminopropyltriethoxysilane (CAS 919-30-2), nano-alumina (A800207, 30nm particle size), 4,4'-(hexafluoroisopropene)phthalic anhydride (CAS 1107-00-2), and 2,2-bis(4- The CAS number for (aminophenyl)hexafluoropropane is 1095-78-9; the CAS number for 6-amino-1-mercaptohexane hydrochloride is 31098-40-5; the CAS number for N-phenyl-N'-cyclohexyl-p-phenylenediamine is 101-87-1; the CAS number for 4,4'-diaminodiphenyl ether is 101-80-4; the item number for bitumen is WB93918; the item number for ethylene vinyl acetate is S45075; the item number for polyvinyl chloride is S51649; and the item number for styrene-butadiene-styrene (SBS) is PA07722.

[0024] The preparation method of aminated alumina is as follows: 0.045 parts of 3-aminopropyltriethoxysilane are added to 90wt% aqueous ethanol solution, the pH is adjusted to 4, 1.2 parts of nano-alumina are added and mixed evenly, and the reaction is carried out at 60℃ for 4 hours. After cooling to room temperature, centrifugation, washing and drying are performed to obtain aminated alumina.

[0025] The method for preparing the slurry is as follows: S1: (1) Weigh zinc nitrate and titanium dioxide in a mass ratio of 3:5, and ball mill them for 30 minutes. Then add them to a 2M sodium hydroxide aqueous solution and mix them evenly for 1 hour. Then calcine them at 600℃ for 2 hours to obtain composite nanoparticles. (2) The composite nanoparticles were ultrasonically dispersed in toluene solution and reacted at 100°C for 20 hours. Then, 3-aminopropyltriethoxysilane was added and the reaction was continued for 8 hours to obtain aminated composite nanoparticles. The mass ratio of the composite nanoparticles to 3-aminopropyltriethoxysilane was 1:0.05. (3) Add 4 parts of aminated composite nanoparticles to 60 parts of N,N'-dimethylformamide and mix evenly. Add 4.4 parts of 4,4'-(hexafluoroisopropene) phthalic anhydride. Under nitrogen protection, react at room temperature for 30 minutes, then heat to 150°C and react for 2 hours. Add 6 parts of 2,2-bis(4-aminophenyl)hexafluoropropane and mix evenly. Heat to 180°C and continue to react for 6 hours to obtain composite nanoparticle polymer. S2: 15 parts of composite nanoparticle polymer, 3 parts of N-phenyl-N'-cyclohexyl-p-phenylenediamine, and 45 parts of N,N'-dimethylformamide were ball-milled for 2 hours at 35°C and 800 rpm to obtain a slurry.

[0026] Example 1: A manufacturing process for an asphalt-modified ethylene vinyl acetate waterproof membrane, comprising the following steps: S1: (1) After cutting the polyester fabric, place it in deionized water at 55°C for 1 hour, then place it in acetone solution, ultrasonically clean it, dry it, place it in slurry, and ultrasonically soak it for 15 minutes at 40°C to obtain pre-made polyester fabric; (2) Clean and dry the mesh fabric to obtain pre-made mesh fabric. S2: (1) 0.5 parts of 6-amino-1-mercaptohexane hydrochloride, 2.7 parts of ethylene vinyl acetate copolymer, and 0.002 parts of AIBN were added to 25 parts of tetrahydrofuran and mixed evenly. The mixture was then irradiated under a 350nm, 100W UV lamp for 2 hours to obtain an intermediate product; (2) 4.4 parts of 4,4'-(hexafluoroisopropene) phthalic anhydride were added to 25 parts of N,N'-dimethylformamide and mixed evenly to obtain solution A; under nitrogen protection, 1.5 parts of 4,4'-diaminodiphenyl ether were added to 25 parts of N,N'-dimethylformamide and mixed evenly. Solution A was added and reacted at room temperature for 35 minutes. The temperature was raised to 160℃ and reacted for 2 hours. 4.39 parts of intermediate product and 3.2 parts of aminated alumina were ball-milled and added. The mixture was then reacted at 195℃ for 6.5 hours to obtain modified ethylene vinyl acetate copolymer; (2) Weigh the asphalt and the modified ethylene vinyl acetate copolymer at a mass ratio of 3:1; heat the asphalt to a molten state at 150°C, add the modified ethylene vinyl acetate copolymer, raise the temperature to 185°C, mix evenly, shear at 6000 r / min for 30 minutes, then shear at 500 r / min for 20 minutes, and incubate at 165°C for 1 hour to obtain the modified asphalt; (3) Mix 6 parts of polyvinyl chloride, 10 parts of modified bitumen and 8 parts of styrene-butadiene-styrene evenly, then plasticize and extrude to obtain the matrix roll material; S3: The base roll material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then composited, pulled, widened and wound up to obtain the waterproof roll material. The composite processing conditions are as follows: hot pressing: temperature 180℃, pressure 4MPa, time 10 minutes; cold pressing: temperature 6℃, pressure 2MPa, time 15 minutes. The process conditions for plasticizing extrusion are as follows: feeding section 175℃, plasticizing end 195℃, metering section 200℃, die temperature 190℃, and screw speed 45r / min.

[0027] Example 2: A manufacturing process for an asphalt-modified ethylene vinyl acetate waterproof membrane, comprising the following steps: S1: (1) After cutting the polyester fabric, place it in deionized water at 55°C for 1 hour, then place it in acetone solution, ultrasonically clean it, dry it, place it in slurry, and ultrasonically soak it for 15 minutes at 40°C to obtain pre-made polyester fabric; (2) Clean and dry the mesh fabric to obtain pre-made mesh fabric. S2: (1) 0.5 parts of 6-amino-1-mercaptohexane hydrochloride, 2.7 parts of ethylene vinyl acetate copolymer, and 0.002 parts of AIBN were added to 25 parts of tetrahydrofuran and mixed evenly. The mixture was then irradiated under a 350nm, 100W UV lamp for 2 hours to obtain an intermediate product; (2) 4.4 parts of 4,4'-(hexafluoroisopropene) phthalic anhydride were added to 25 parts of N,N'-dimethylformamide and mixed evenly to obtain solution A; under nitrogen protection, 1.5 parts of 4,4'-diaminodiphenyl ether were added to 25 parts of N,N'-dimethylformamide and mixed evenly. Solution A was added and reacted at room temperature for 35 minutes. The temperature was raised to 160℃ and reacted for 2 hours. 4.39 parts of intermediate product and 3.2 parts of aminated alumina were ball-milled and added. The mixture was then reacted at 195℃ for 6.5 hours to obtain modified ethylene vinyl acetate copolymer; (2) Weigh the asphalt and the modified ethylene vinyl acetate copolymer at a mass ratio of 3:1; heat the asphalt to a molten state at 150°C, add the modified ethylene vinyl acetate copolymer, heat to 185°C, mix evenly, shear at 6000 r / min for 35 minutes, then shear at 500 r / min for 25 minutes, and incubate at 165°C for 1.2 hours to obtain the modified asphalt; (3) After uniformly mixing 67 parts of polyvinyl chloride, 12.5 parts of modified bitumen and 8.2 parts of styrene-butadiene-styrene, plasticize and extrude to obtain the matrix roll material; S3: The base roll material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then composited, pulled, widened and wound up to obtain the waterproof roll material. The composite processing conditions are as follows: hot pressing: temperature 180℃, pressure 4MPa, time 10 minutes; cold pressing: temperature 6℃, pressure 2MPa, time 15 minutes. The process conditions for plasticizing extrusion are as follows: feeding section 175℃, plasticizing end 195℃, metering section 200℃, die temperature 190℃, and screw speed 45r / min.

[0028] Example 3: A manufacturing process for an asphalt-modified ethylene vinyl acetate waterproof membrane, comprising the following steps: S1: (1) After cutting the polyester fabric, place it in deionized water at 55°C for 1 hour, then place it in acetone solution, ultrasonically clean it, dry it, place it in slurry, and ultrasonically soak it for 15 minutes at 40°C to obtain pre-made polyester fabric; (2) Clean and dry the mesh fabric to obtain pre-made mesh fabric. S2: (1) 0.5 parts of 6-amino-1-mercaptohexane hydrochloride, 2.7 parts of ethylene vinyl acetate copolymer, and 0.002 parts of AIBN were added to 25 parts of tetrahydrofuran and mixed evenly. The mixture was then irradiated under a 350nm, 100W UV lamp for 2 hours to obtain an intermediate product; (2) 4.4 parts of 4,4'-(hexafluoroisopropene) phthalic anhydride were added to 25 parts of N,N'-dimethylformamide and mixed evenly to obtain solution A; under nitrogen protection, 1.5 parts of 4,4'-diaminodiphenyl ether were added to 25 parts of N,N'-dimethylformamide and mixed evenly. Solution A was added and reacted at room temperature for 35 minutes. The temperature was raised to 160℃ and reacted for 2 hours. 4.39 parts of intermediate product and 3.2 parts of aminated alumina were ball-milled and added. The mixture was then reacted at 195℃ for 6.5 hours to obtain modified ethylene vinyl acetate copolymer; (2) Weigh the asphalt and the modified ethylene vinyl acetate copolymer at a mass ratio of 3:1; heat the asphalt to a molten state at 150°C, add the modified ethylene vinyl acetate copolymer, raise the temperature to 185°C, shear at a speed of 6000 r / min for 35 minutes, shear at a speed of 500 r / min for 25 minutes, and incubate at 165°C for 1.2 hours to obtain the modified asphalt; (3) After uniformly mixing 70 parts of polyvinyl chloride, 15 parts of modified bitumen and 12 parts of styrene-butadiene-styrene, plasticize and extrude to obtain the matrix roll material; S3: The base roll material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then composited, pulled, widened and wound up to obtain the waterproof roll material. The composite processing conditions are as follows: hot pressing: temperature 180℃, pressure 4MPa, time 10 minutes; cold pressing: temperature 6℃, pressure 2MPa, time 15 minutes. The process conditions for plasticizing extrusion are as follows: feeding section 175℃, plasticizing end 195℃, metering section 200℃, die temperature 190℃, and screw speed 45r / min.

[0029] Comparative Example 1 is based on Example 2, in which aminated composite nanoparticles are introduced into the slurry alone; S1: (1) After cutting the polyester fabric, place it in deionized water at 55°C for 1 hour, then place it in acetone solution, ultrasonically clean it, dry it, place it in slurry, and ultrasonically soak it for 15 minutes at 40°C to obtain pre-made polyester fabric; (2) Clean and dry the mesh fabric to obtain pre-made mesh fabric. S2: (1) 0.5 parts of 6-amino-1-mercaptohexane hydrochloride, 2.7 parts of ethylene vinyl acetate copolymer, and 0.002 parts of AIBN were added to 25 parts of tetrahydrofuran and mixed evenly. The mixture was then irradiated under a 350nm, 100W UV lamp for 2 hours to obtain an intermediate product; (2) 4.4 parts of 4,4'-(hexafluoroisopropene) phthalic anhydride were added to 25 parts of N,N'-dimethylformamide and mixed evenly to obtain solution A; under nitrogen protection, 1.5 parts of 4,4'-diaminodiphenyl ether were added to 25 parts of N,N'-dimethylformamide and mixed evenly. Solution A was added and reacted at room temperature for 35 minutes. The temperature was raised to 160℃ and reacted for 2 hours. 4.39 parts of intermediate product and 3.2 parts of aminated alumina were ball-milled and added. The mixture was then reacted at 195℃ for 6.5 hours to obtain modified ethylene vinyl acetate copolymer; (2) Weigh the asphalt and the modified ethylene vinyl acetate copolymer at a mass ratio of 3:1; heat the asphalt to a molten state at 150°C, add the modified ethylene vinyl acetate copolymer, heat to 185°C, mix evenly, shear at 6000 r / min for 35 minutes, then shear at 500 r / min for 25 minutes, and incubate at 165°C for 1.2 hours to obtain the modified asphalt; (3) After uniformly mixing 67 parts of polyvinyl chloride, 12.5 parts of modified bitumen and 8.2 parts of styrene-butadiene-styrene, plasticize and extrude to obtain the matrix roll material; S3: The base roll material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then composited, pulled, widened and wound up to obtain the waterproof roll material. The composite processing conditions are as follows: hot pressing: temperature 180℃, pressure 4MPa, time 10 minutes; cold pressing: temperature 6℃, pressure 2MPa, time 15 minutes. The process conditions for plasticizing extrusion are as follows: feeding section 175℃, plasticizing end 195℃, metering section 200℃, die temperature 190℃, and screw speed 45r / min.

[0030] Comparative Example 2 is based on Example 2, except that the modified ethylene vinyl acetate copolymer is replaced with ethylene vinyl acetate copolymer; S1: (1) After cutting the polyester fabric, place it in deionized water at 55°C for 1 hour, then place it in acetone solution, ultrasonically clean it, dry it, place it in slurry, and ultrasonically soak it for 15 minutes at 40°C to obtain pre-made polyester fabric; (2) Clean and dry the mesh fabric to obtain pre-made mesh fabric. S2: (1) Weigh asphalt and ethylene vinyl acetate copolymer at a mass ratio of 3:1; heat asphalt to a molten state at 150°C, add ethylene vinyl acetate copolymer, heat to 185°C, mix evenly, shear at 6000 r / min for 35 minutes, then shear at 500 r / min for 25 minutes, and incubate at 165°C for 1.2 hours to obtain modified asphalt; (2) After uniformly mixing 67 parts of polyvinyl chloride, 12.5 parts of modified bitumen and 8.2 parts of styrene-butadiene-styrene, plasticize and extrude to obtain the matrix roll material; S3: The base roll material and prefabricated polyester fabric are sequentially stacked on the prefabricated mesh fabric, and then composited, pulled, widened and wound up to obtain the waterproof roll material. The composite processing conditions are as follows: hot pressing: temperature 180℃, pressure 4MPa, time 10 minutes; cold pressing: temperature 6℃, pressure 2MPa, time 15 minutes. The process conditions for plasticizing extrusion are as follows: feeding section 175℃, plasticizing end 195℃, metering section 200℃, die temperature 190℃, and screw speed 45r / min.

[0031] Testing: The waterproof membranes of Examples 1-3 and Comparative Examples 1-2 were tested for water absorption (%), heat resistance, low temperature resistance, and peel strength (N / mm) after heat aging. The test results are shown in Table 1. Table 1

[0032] Conclusions: Comparative Example 1, based on Example 2, introduced aminated composite nanoparticles into the slurry alone, leading to a decrease in the low-temperature resistance, heat resistance, peel strength, and water absorption of the waterproof membrane. Comparative Example 2, based on Example 2, replaced the modified ethylene vinyl acetate copolymer with ethylene vinyl acetate copolymer, which reduced the interfacial compatibility between polyvinyl chloride and asphalt, thereby affecting the low-temperature resistance, heat resistance, peel strength, and water absorption of the waterproof membrane.

[0033] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the spirit and principles of the present invention and within the technical scope disclosed in this application should be included within the scope of protection of this application. Where there is no conflict, the embodiments and features described in the embodiments of this application can be combined with each other. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A process for manufacturing asphalt-modified ethylene vinyl acetate waterproofing membrane, characterized in that: The steps include: S1: (1) washing and drying the polyester cloth, placing it in a slurry at 40-50°C, and ultrasonically immersing it for 15-20 minutes to obtain a prefabricated polyester cloth; (2) washing and drying the mesh cloth to obtain a prefabricated mesh cloth; S2: (1) heating the asphalt at 140-150°C to a molten state, adding the modified ethylene vinyl acetate copolymer, raising the temperature to 180-185°C, mixing evenly, shearing at a speed of 4500-6000 r / min for 20-30 minutes, then shearing at a speed of 500-600 r / min for 20-30 minutes, and incubating at 160-170°C for 1-2 hours to obtain modified asphalt; (2) uniformly mixing polyvinyl chloride, modified asphalt and styrene-butadiene-styrene, plasticizing and extruding the mixture to obtain a base coil; S3: stacking the base coil and the prefabricated polyester cloth on the prefabricated mesh cloth in sequence, and performing compound treatment, pulling, width adjustment, and rolling in sequence to obtain the waterproof coil.

2. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 1, characterized in that: The mass ratio of the asphalt to the modified ethylene vinyl acetate copolymer is (3-4):1; the raw materials of the base coil include the following components: by weight, 60-70 parts of polyvinyl chloride, 10-15 parts of modified asphalt, and 8-12 parts of styrene-butadiene-styrene.

3. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 1, characterized in that: The preparation method of the modified ethylene vinyl acetate copolymer is as follows: (1) adding 6-amino-1-mercaptohexane hydrochloride, ethylene vinyl acetate copolymer and AIBN into tetrahydrofuran, uniformly mixing, and irradiating under a 350nm, 100W ultraviolet lamp for 2-3 hours to obtain an intermediate product; (2) adding 4,4'-(hexafluoroisopropylene) diphthalic anhydride into N,N'-dimethylformamide and uniformly mixing to obtain solution A; under nitrogen protection, adding 4,4'-diaminodiphenyl ether into N,N'-dimethylformamide and uniformly mixing, adding solution A, reacting at room temperature for 30-40 minutes, heating to 150-160°C and reacting for 2-3 hours, adding the intermediate product and amino alumina and uniformly mixing, and continuing to react at 180-200°C for 6-8 hours to obtain the modified ethylene vinyl acetate copolymer.

4. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 3, characterized in that: The raw materials of the intermediate product include the following components: by weight, 0.5-0.8 parts of 6-amino-1-mercaptohexane hydrochloride, 2-3 parts of ethylene vinyl acetate copolymer, 0.002-0.003 parts of AIBN, and 20-40 parts of tetrahydrofuran; The raw materials of the modified ethylene vinyl acetate copolymer include the following components: by weight, 4.42-4.45 parts of 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 40-50 parts of N,N'-dimethylacetamide, 2-2.2 parts of 4,4'-diaminodiphenyl ether, 4.39-4.4 parts of intermediate products, and 3-5 parts of amino aluminum oxide.

5. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 1, characterized in that: The preparation method of the slurry is: S1: (1) After mixing zinc nitrate and titanium dioxide by ball milling for 20-30 minutes, add them to a 2-3M sodium hydroxide aqueous solution and mix them evenly for 1-2 hours, and calcine them at 600-650°C for 2-3 hours to obtain composite nanoparticles; (2) Ultrasonic disperse the composite nanoparticles in a toluene solution, react at 100-120°C for 20-22 hours, add 3-aminopropyltriethoxysilane, and continue to react for 8-10 hours to obtain amino composite nanoparticles; (3) Add the amino composite nanoparticles to N,N'-dimethylformamide and mix them evenly, add 4,4'-(hexafluoroisopropylene) diphthalic anhydride, react at room temperature for 30-40 minutes under nitrogen protection, heat to 150-160°C, react for 2-3 hours, mix 2,2-bis(4-aminophenyl)hexafluoropropane evenly, heat to 180-200°C and continue to react for 6-8 hours to obtain a composite nanoparticle polymer; S2: The composite nanoparticle polymer, N-phenyl-N'-cyclohexyl-p-phenylenediamine and N,N'-dimethylformamide are ball-milled for 2-4 hours at a temperature of 30-40° C. and a rotation speed of 800-1000 rpm to obtain a slurry.

6. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 5, characterized in that: The mass ratio of zinc acetate to titanium dioxide is 3:(5-7); the mass ratio of the composite nanoparticles to 3-aminopropyltriethoxysilane is 1:(0.05-0.08); the raw materials of the composite nanoparticle polymer include the following components: by weight, 4-6 parts of amino composite nanoparticles, 4.4-4.5 parts of 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 6-7 parts of 2,2-bis(4-aminophenyl)hexafluoropropane, and 60-70 parts of N,N'-dimethylformamide.

7. The manufacturing process of the asphalt modified ethylene vinyl acetate waterproofing membrane according to claim 5, characterized in that: The raw materials of the slurry include the following components: by weight, 15-20 parts of composite nanoparticle polymer, 3-5 parts of N-phenyl-N'-cyclohexyl-p-phenylenediamine, and 40-60 parts of N,N'-dimethylformamide.

8. A waterproofing membrane prepared according to the manufacturing process of an asphalt-modified ethylene vinyl acetate waterproofing membrane according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing ethylene-vinyl acetate copolymer asphalt waterproof roll

    CN107938372A

  • SBS elastomer modified asphalt waterproofing coiled material and preparation method thereof

    CN108407424A

  • High-strength TPO waterproof coiled material and preparation method thereof

    CN117565526A